Mots cachés: Autobiography in Cocteau's and Poulenc's La Voix humaine - Clifton, Keith (Canadian University Music Review / Revue de musique des universités canadiennes, 2001)
Poulenc's Dialogues des Carmélites has been consistently identified as the summit of his operatic works. Such an assessment has assured that his final opera, La Voix humaine, based on Cocteau's monodrama, has been overlooked, the impetus for its composition inadequately defined. Musically, La Voix humaine employs a complex tonal language unprecedented in Poulenc's compositional arsenal. Rather than advancing the interpretation that Poulenc composed Voix out of loyalty to Cocteau, I propose that the opera represents his final attempt to come to terms with his homosexuality. Numerous references in correspondence expose the opera as a mirror of Poulenc's emotional life. Poulenc and Cocteau's employment of gay camp also informs the work and provides a glimpse into possible hidden meanings. A closer examination of this neglected work reveals new insights into Poulenc's troubled and elusive personality.